PEMBENTUKAN SIKAP SOSIAL SISWA MELALUI PEMBELAJARAN IPS DI SMP BRAWIJAYA SMART SCHOOL MALANG - Miftahusya’ian, Moh.; Fitriana, Wiwin Nuris; Mulyoto, Galih Puji (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The objectives of this study were to: (1) describe the process of forming students' social attitudes through social studies learning methods for class VII SMP Brawijaya Smart School Malang, (2) describe forms of student social attitudes formed through social studies learning methods for class VII SMP Brawijaya Smart School Malang, (3) describes the change in students' social attitudes after the process of forming social attitudes through social studies learning methods for class VII SMP Brawijaya Smart School Malang. This research uses a qualitative research approach with a descriptive qualitative research type. The data collection methods used were observation, interview, and documentation. The author acts as an observer in observation. In this study, researchers conducted data analysis through data reduction, data presentation, and verification (drawing conclusions). The results showed that (1) the process of forming social attitudes of seventh-grade students of SMP Brawijaya Smart School Malang through social studies learning methods was carried out by the teacher by involving two factors, namely internal factors (students) and external factors (school, home, and community environment. ), (2) the forms of student social attitudes can be seen by the existence of activities in class and outside the classroom (extracurricular activities) as well as school culture and regulations, and school culture (3) as a whole from some of the social attitudes of students who experience the most visible changes, namely changes in manners and disciplineKeywords: Social Attitudes; Social Studies Learning Method